Joint Forest Management in Kamraj Forest Division Zangli Kupwara Kashmir (J & K): a Case Study - Razvi, Sajad; Agarwal, Rashmi; Nautiyal, S.; Dar, M. Ayoub (Indian Forester, 2011)
The policy directives issued by the government of India from time to time since the announcement of the National Forest Policy, 1988 indicate the existence of a ’learning curve’ in the process of implementation of JFM in India. This paper gives an account about the status of Joint Forest Management (JFM) in the Kamraj Forest Division, Zangli Kupwara of Jammu and Kashmir. The land holding pattern in the state is totally different from the other states as, most of the land belongs to forest department. The JFM was formallv adopted in Jamp;K State by issuing a notification SRO 61 dated 19-03-1992. The concept of JFM caught up in the State through formation of VFCs. At present IS99 VFCs are functioning over the state, both with social forestry projects and the territorial wings of forest department and around 10000 ha of land is under rehabilitation with the assistance and participation of VFCs. In Kamraj Forest Division, 58 VFC’s are working and an area of1500 ha land has been rehabilited by National Afforestration Programme from 2003 to 2007.